2020
DOI: 10.1007/s00125-020-05164-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and management of COVID-19 among patients with diabetes: an appraisal of the literature

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has emerged as one of the greatest challenges faced by humankind in the recent past. People with diabetes and related comorbidities are at increased risk of its complications and of COVID-19-related death. Older age, multi-morbidity, hyperglycaemia, cardiac injury and severe inflammatory response are predictors of poor outcome. The complex interplay between COVID-19, diabetes and the effects of related therapies is being explored. Most patients experience a mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
184
2
34

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(222 citation statements)
references
References 69 publications
2
184
2
34
Order By: Relevance
“…From a clinical practice standpoint patient counseling should include discussing glycemic goals and sick day insulin dosing regimens, as well as adequate hydration and maintaining access to food (including nonperishable items, glucose and electrolyte tablets). Furthermore, adoption and continuation of a healthy diet and recommended 150 minutes of weekly exercise such as indoor walking and other physical distancing compatible exercises should be encouraged [56]. Recommended vaccinations for influenza, pneumococcal and other infections should be emphasized (based on CDC or equivalent local authority guidelines).…”
Section: Clinical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…From a clinical practice standpoint patient counseling should include discussing glycemic goals and sick day insulin dosing regimens, as well as adequate hydration and maintaining access to food (including nonperishable items, glucose and electrolyte tablets). Furthermore, adoption and continuation of a healthy diet and recommended 150 minutes of weekly exercise such as indoor walking and other physical distancing compatible exercises should be encouraged [56]. Recommended vaccinations for influenza, pneumococcal and other infections should be emphasized (based on CDC or equivalent local authority guidelines).…”
Section: Clinical Approachmentioning
confidence: 99%
“…In these patients less aggressive insulin regimens with the aim of minimizing glycosuria, dehydration, and electrolyte disturbances may be more appropriate, however clinical judgment combined with continuing assessment of clinical status that includes changes in the trajectory of glucose measures, illness severity, nutritional status, or concomitant medications that might affect glucose levels, should be incorporated into medical decision making. Furthermore, it is reasonable to discontinue sodium-glucose co-transporter-2 inhibitors (SGLT-2i) that have been associated with intravascular volume depletion and increased risk of euglycemic ketosis [56]. Discontinuation of sulfonylureas is also advisable, particularly in critical patients, where drug renal clearance may be compromised [56].…”
Section: Clinical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study suggested that COVID-19 patients using ACEIs and ARBs during hospitalization will not increase the risk of death [18]. As for diabetes, though, people with diabetes might be at increased risk of severe disease, no existing conclusive evidence supports the discontinuation of ACEIs, ARBs, or thiazolidinediones in people with diabetes for precaution of COVID-19 [19,20]. Katulanda et al proposed that, in addition to the direct vulnerability to severe COVID-19, people with diabetes should be recognized as a vulnerable group for complicated disease and are at risk since the potential limited access to insulin, blood glucose monitoring equipment, and other healthcare which would be impacted by the COVID-19 [19].…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…As for diabetes, though, people with diabetes might be at increased risk of severe disease, no existing conclusive evidence supports the discontinuation of ACEIs, ARBs, or thiazolidinediones in people with diabetes for precaution of COVID-19 [19,20]. Katulanda et al proposed that, in addition to the direct vulnerability to severe COVID-19, people with diabetes should be recognized as a vulnerable group for complicated disease and are at risk since the potential limited access to insulin, blood glucose monitoring equipment, and other healthcare which would be impacted by the COVID-19 [19]. Therefore, we believe that patients with hypertension and diabetes should pay more attention to the prevention against SARS-CoV-2, and su cient medical support to these vulnerable people is necessary.…”
Section: Treatment and Prognosismentioning
confidence: 99%